Coral reef aorta, emergency surgical: case report and literature review - Belczak,Sergio Quilici (2014)
Coral reef aorta is described as an uncommon entity characterized by the presence of coarse calcifications, which are developed in the visceral aorta. These calcifications grow toward the lumen of the artery and can result in significant stenosis, so that causing malperfusion of the lower limbs, visceral ischemia or hypertension secondary to renal involvement. We report here a case of a 54-year-old patient with coral reef aorta and symptomatic. The clinical presentation of the patient required the surgical approach. A review of literature in major databases was conducted to compare health-related aspects of the disease presentation and management. Coral reef aorta should be considered as the diagnosis for patients with visceral and limbs ischemia. The approach in our case was consistent with other studies previously published in the literature.